The Effect of Personalized Feedback on Small Enterprises' Finances in Uganda - Helke Seitz; Lukas Menkhoff; Antonia Grohmann (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This study examines the effect of two different finance trainings on business outcomes. The first training is based on a "rule-of-thumb" approach, teaching simple financial rules. The content of the second training is exactly the same but additionally provides personalized feedback on past financial performance and practices of the entrepreneur. Running a small intervention targeting 500 small and micro entrepreneurs in Kampala (Uganda), we find that the additional personalized feedback significantly improves overall savings by 0.279 standard deviation units. Analysing the specific feedbacks provided we find that not all feedbacks work in the same way to change behavior in the desired direction.
Keywords: O12; D22; O16; L26; 330; Financial Training; Feedback; Small Business Growth; Economic Development